PENGARUH MODEL PAKEM TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS III SDN GUGUS II GUNUNG SARI - Ardiansari, Rini; Ratnadi, Ratnadi (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2018)
This research is motivated by a situation where teachers need to design and implement learning using learning models that enable students to learn more actively and create meaningful impressions in the hope that learning outcomes can be achieved. The aim of this research is to prove whether there is an influence of the standard model on science learning outcomes for class III students at SDN Gugus II Gunung Sari. This research is a quasi-experimental research (quasi-experimental design) with a nonequivalent control group design. The population of this research were all students in class III of SDN Gugus II Gunung Sari, totaling 184 students, and the research sample was taken using the purposive sampling technique, totaling 48 students, namely classes IIIA and IIIB. The data collection technique in this research is using tests and documentation. Post-test data analysis in this study used the t test to determine whether there was an effect of treatment in the experimental group. Based on the results of statistical analysis calculations, tcount results of 3.891> ttable = 2.014 at a significance level of 5% can be obtained. These results prove that there is an influence of the Pakem Model on Science Learning Outcomes in Class III Students at SDN Gugus II Gunung Sari.